Analisis Environment, Social, Governance dan Struktur Kepemilikan Terhadap Nilai Perusahaan Dengan Pemoderasi Kekuatan CEO - Handoko, Jesica; Pradinata, Ingrid Agustina; Mokoginta, Dirgantara Dahana (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The long-term sustainability of a company really depends on how the company maintains its company value. Companies can increase their value by taking care environmental, social and governance (ESG. An ownership structure that includes managerial ownership and institutional ownership can grow company value. This research is quantitative research which aims to evaluate the components that influence company value. The object of this research is non-financial sector companies listed on the Indonesia Stock Exchange in 2020-2022 and publishing ESG score data. The sample in this study consisted of 170 samples selected using purposive sampling technique. The data sources used are annual reports along with company financial reports. The data analysis technique in this research uses multiple linear regression analysis. The results of this research show that institutional ownership has a positive impact on company value, while environmental, social, governance and managerial ownership have no impact on company value. The results moderated by CEO power show that the environment, social, governance and ownership structure in terms of institutional ownership and managerial ownership do not have an impact on firm value, indicating that CEO power is not able to strengthen the relationship between environment, social, governance and ownership structure, both institutional ownership and managerial ownership. on company value.